Clinicopathological correlation and expression of PD-L1 in cervical carcinoma: An immunohistochemical study - Arshdeep Kaur; Mansimran Kaur; Akanksha Singh; Menka Khanna; Karamjit Singh; Ishaan Khanna (Journal of Pathology of Nepal)
Background: Cervical cancer is the fourth most common cancer in women globally and the second leading cause of cancer deaths in India. Risk factors include HPV infection, smoking, long-term oral contraceptive use, early pregnancy, nulliparity, and multiple sexual partners. Programmed cell death-1/programmed cell death-ligand 1 (PD-1/PD-L1) inhibitors may improve outcomes in recurrent, persistent, or metastatic cervical cancer. This study aimed to determine the various histological types of cervical carcinoma, determine PD-L1 expression, correlate it with PDL1-positive TILs, and provide insight into clinicopathological parameters such as age, stage, etc.